QbD Approach For Anti-Cancer Drugs - A Review - Thanigainathan, Sudarvizhi; Ramalingan, Sangamithra; Meyyanathan, Subramanianainar; Babu, Basavan (Current Pharmaceutical Analysis, 2022)
Abstract: Background: Several analytical approaches for assessing anti-cancer drugs in pharmaceutical formulations have been developed over the last few years. QbD plays an important role in establishing accurate analytical methods to analyze anti-cancer compounds. Quality by Design has become a risk analysis and a science-based strategy, implemented by experimental methods to optimize system output with known variables for data. The influence of highly complex and correlations of input variables on the output reactions of pharmaceutical drugs and empirical approaches have been widely used to explain the design of experiments. Objectives: The efficiency of the anti-cancer drugs and their formulation in the various dosage forms has been made convenient with the help of QbD designs such as Plackett Burman, full factorial design, etc. QbD contains various steps, which help enhance and sustain the quality of the drug in its dosage form. Conclusion: This review covers a basic, efficient, and accurate analytical approach technique using Quality by Design for anti-cancer drugs. Thus, an outline of the experimental methods used in anti-cancer drugs was identified and discussed.
Keywords: variables